Implementasi Software Pvsyst Untuk Perancangan PLTS Offgrid Di Kecamatan Binong Kabupaten Subang - Wendy Supriatna (Jurnal Kendali Teknik dan Sains, 2023)
The Meteorology, Climatology and Geophysics Agency predicts a long dry season will occur in Subang Regency in 2023 with the potential for El Nino for the next one year. Subang's solar energy potential reaches 4.8 kWh/M2. Solar energy is used to irrigate rice fields in Binong. The energy produced by solar panels is converted to motion energy which is used to suck up water. In this study it was found that solar energy produced by solar panels can drive an electric motor with a load of 2.4 kW for 6 hours which is used to meet the water needs in the fields.